2013
DOI: 10.1002/jrs.4275
|View full text |Cite
|
Sign up to set email alerts
|

Pure rotational Coherent anti‐Stokes Raman spectroscopy of water vapor and its relevance for combustion diagnostics

Abstract: In this work, we report for the first time the rotational coherent anti‐Stokes Raman spectroscopy (CARS) spectrum of water vapor, recorded through experiments at 400 K and 670 K for Raman shifts up to 600 cm−1. Using the standard dual‐broadband pure rotational CARS approach, the resonant structure was overwhelmed by a strong non‐resonant background. By employing a polarization technique, this background could be suppressed and the resonant structure discerned. The spectral line structure matched spectra from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Other groups extended CARS to new molecules and new pieces of information that can be gained. Bengtsson et al implemented strategies for utilizing the rotational CARS signals of nitrous oxide and water vapor . Although both species are not desirable target species, for example, for thermometry, their signals may interfere with that of nitrogen or oxygen.…”
Section: Applications To Gas‐phase and Combustion Systemsmentioning
confidence: 99%
“…Other groups extended CARS to new molecules and new pieces of information that can be gained. Bengtsson et al implemented strategies for utilizing the rotational CARS signals of nitrous oxide and water vapor . Although both species are not desirable target species, for example, for thermometry, their signals may interfere with that of nitrogen or oxygen.…”
Section: Applications To Gas‐phase and Combustion Systemsmentioning
confidence: 99%
“…[17,22] Oxygen is abundant in the typically lean oxy-fuel combustion environment and exhibits a large Raman cross-section compared with H 2 O for instance. [5,19,23,24] However, the knowledge about empirical parameters based on S-branch Raman linewidth of oxygen is small. [21,25] Up to now the S-branch evaluation is based on Q-branch linewidth data, which can deviate from the S-branch data.…”
Section: Introductionmentioning
confidence: 99%
“…Their measurements were carried out at 400 K and 670 K for Raman shifts up to 600 cm −1 . They found that due to the weak resonant signal, water vapor is an unsuitable candidate for CARS thermometry and relative concentration measurements in combustion . Rocha‐Mendoza et al .…”
Section: Introductionmentioning
confidence: 99%